Orchestrating Sufism: The Transculturation of Ottoman Aesthetic Traditions in Indonesian Muslims - Sunarto, Sunarto; Habiba Abror, Robby (ESENSIA: Jurnal Ilmu-Ilmu Ushuluddin, 2022)
This article provides an understanding of the aesthetic relationship between the Ottoman and Indonesia. Turkey was instrumental in Islamization and political support for Indonesia. Islam came to Indonesia in the 13th century, which was brought by merchants of the Middle East and Ottoman Turks. They used a variety of dawah mediums, including economics, politics, social, and arts. Many sources write about the central role of traders from the Middle East in the Islamization of Indonesia, yet few resources give explanations of the role of Turkish traders and preachers. Using the descriptive analysis method, this article argues that Turkey has had a strong influence on Sufism in Indonesia. The main instrument in this research is library observation. This study found that the Ottoman Turks influenced aesthetic-sufistic interactions in Indonesia. In addition, the Ottoman Turkey with Sufism from Mevlana Jalāl ad-Dīn Rūmī has introduced music to Indonesia, which includes recitative poetry sung, Turkish musical instruments, and the Sufistic Whirling Darvish dance of Mevlevi Rūmī sufism order. The influence of Turkey spread to the Javanese and Malay-speaking Sumatran people.